2017
DOI: 10.1111/cch.12528
|View full text |Cite
|
Sign up to set email alerts
|

The association between pediatric injury risks and parenting behaviours

Abstract: Results from this study highlight the importance of supporting younger mothers and educating parents on effective parenting strategies when trying to prevent unintentional injury risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…Next to the fact that the storage cabinets for household chemicals should be lockable and elevated, dedicated cleaning cabinets provide a clear context for children and help them associate the stored products with household chemicals. This suggestion is in line with multiple other studies on the prevention of unintentional injuries with household chemicals (Beirens et al, 2006;Gibbs et al, 2005;Jaques et al, 2018;Morrongiello et al, 2006). Finally, the results of this study suggest that the way parents handle household chem- icals at home might not influence children's ability to correctly categorize household chemicals.…”
Section: Discussionsupporting
confidence: 90%
“…Next to the fact that the storage cabinets for household chemicals should be lockable and elevated, dedicated cleaning cabinets provide a clear context for children and help them associate the stored products with household chemicals. This suggestion is in line with multiple other studies on the prevention of unintentional injuries with household chemicals (Beirens et al, 2006;Gibbs et al, 2005;Jaques et al, 2018;Morrongiello et al, 2006). Finally, the results of this study suggest that the way parents handle household chem- icals at home might not influence children's ability to correctly categorize household chemicals.…”
Section: Discussionsupporting
confidence: 90%
“…To the best of our efforts, we searched the literature for research on a relationship between child maltreatment and unintentional injuries, but found little. Studies in the clinical setting have pointed at the influence of parenting behavior and supervisory neglect [ 27 , 28 ], which is in line with our findings of doubled odds for unintentional injuries leading to health- or dental care in the last year among adolescents reporting parental neglect.…”
Section: Discussionsupporting
confidence: 90%
“…Hay una discreta elevación de la incidencia de mordeduras y otras lesiones entre agosto y enero, meses con menor actividad escolar y mayor tiempo de permanencia en el hogar por feriados, fechas conmemorativas, actividades comerciales de fin de año, que tienen en común un descuido de los niños. 9,10 Se hace notar que, de marzo a julio del 2020, el país implementó una cuarentena rígida con confinamiento y cierre de actividades escolares hasta finales del 2021, lo que se relacionó con un incremento de los casos.…”
Section: Discussionunclassified